A high-frequency quasi-wideband antenna sensor for partial discharge detection - Lin, Minyi (Nanyang Technological University, 2024)
Partial discharge (PD) detection is significant for ensuring the reliability, safety, and longevity of electrical systems, offering the ability for proactive maintenance and minimizing the risk of catastrophic failures across diverse industrial applications. The radiofrequency (RF) detection method is the most widely utilized approach, covering a spectrum from high-frequency to ultra-high frequency bands. RF detection’s key advantage lies in its immunity to electromagnetic interference (EMI). However, designing antennas for high frequencies presents a challenge, requiring a balance between achieving a wide-band frequency and maintaining a compact volume. This thesis begins with an in-depth categorization of existing PD detection methods, presenting a comprehensive overview of design structures for high-frequency (HF), very high-frequency (VHF), and ultra-high-frequency (UHF) sensors. Subsequently, we introduce a novel quasi-wideband switch antenna sensor designed for operation in the high-frequency band. This sensor incorporates two coil ar- rays and four capacitors, controlled by a microcontroller chip. Various coil and capacitor combinations are selected to achieve distinct resonant frequency responses by programming the microcontroller using Arduino IDE. A total of 48 combinations contribute to forming a wide resonant frequency band. Last but not least, the proposed sensor was tested using a vector network analyzer (VNA) in the 48 combinations of capacitors and coils affirming resonant frequency bands within 1-100MHz. Additionally, in an experiment compared with the High-Frequency Current Transformer (HFCT), our designed antenna sensor successfully detects PD signals in the high-frequency band around 25MHz, demonstrating a sensitivity nearly equivalent to that of HFCT. This proposed switch sensor offers several advantages, including 1) wide-band frequency detection, 2) compact size, and 3) relatively high sensitivity.